Information Literacy: A Vital Link in the Research Chain - Sraku-Lartey, Margaret (Ghana Library Journal, 2016)
Information literacy consists of the competencies researchers must have in order to locate, retrieve, evaluate, select, and use information. Information literacy competencies are vital assets researchers must have in order to meet their information needs. These competencies however are developed over time and are essential for lifelong learning. For researchers, the questions that arise relate to how these competencies can be imparted to them and be woven into the fabric of the research agenda. This cannot be done overnight but rather over a period of time so that one can develop an information literate researcher. This paper is a desk study based on the seven pillars of information literacy model developed by the Society of College, National and University Libraries (SCONUL) in the United Kingdom. The model is used to assess the competencies needed by researchers in accessing their information needs. The paper analyses the seven pillars and relates the competencies needed by research scientist’s to existing situation at CSIR -FORIG. Issues discussed include factors to consider when measuring researchers’ competencies and what could be done for those who lack information literacy skills. The model can be used as an instrument to help achieve best practices in information literacy; and provides support mechanisms and training for researchers to enable them play their role in developing their own competencies and their information literacy levels. Results of the study indicate that to make effective use of information resources, researchers must be acquainted with the seven pillars of information literacy and develop self-learning regimes that would equip them with the relevant skills for using information.